2021
DOI: 10.3390/ijerph182413281
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Public Satisfaction with COVID-19 Prevention Services Based on Structural Equation Modeling (SEM): A Study of Nanjing, China

Abstract: Service satisfaction with public policies is an important component of public service quality management, which is of great significance to the improvement of public service quality. Based on an online questionnaire survey and in combination with the characteristics of public policies and services, in this study the influencing factors of residents’ satisfaction with COVID-19 pandemic prevention services were analyzed with structural equation modeling. The results reveal that the data fit the model well, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…M. Kwon, 2020). In addition, it has been found that the policy contents including them in other fields have a close influence on policy satisfaction, supporting the results of this study (W. Chen et al, 2021; D.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…M. Kwon, 2020). In addition, it has been found that the policy contents including them in other fields have a close influence on policy satisfaction, supporting the results of this study (W. Chen et al, 2021; D.…”
Section: Discussionsupporting
confidence: 90%
“…In this process, social equity, market responsiveness, and policy effectiveness were evaluated as major factors in policy evaluation (S. M. Kwon, 2020). In addition, it has been found that the policy contents including them in other fields have a close influence on policy satisfaction, supporting the results of this study (W. Chen et al, 2021;D. H. Kim, 2018).…”
Section: Sports Policy Contents and Satisfactionsupporting
confidence: 89%
“…Health awareness becomes the most important aspect from the customer's point of view, especially when they want to go outside. The preceding study demonstrates that the residents who were seriously affected by the pandemic had greater expectations for the pandemic prevention policies and services (Chen et al 2021). This means prevention services must meet the expectation of customers so that customer satisfaction also increased.…”
Section: Proposed Improvementsmentioning
confidence: 96%
“…Factors such as perceived quality of government interventions and policy expectations have been shown to influence satisfaction with policies (9). Conversely, pre-established views and levels of trust in government have also played a role in predicting expectations, acceptance, and compliance (4).…”
Section: Introductionmentioning
confidence: 99%